Systemic Mastocytosis in a Patient with BCR-ABL1-Positive Chronic Myeloid Leukemia in the Remission Phase. (3rd November 2022) - Fokoloros, Christos; Foukas, Periklis; Georgakopoulos, Nikolaos; Tsakiraki, Zoi; Bouchla, Anthi; Pappa, Vasilliki; Katoulis, Alexandros; Makris, Michael; Papageorgiou, Sotirios
Abstract : Systemic mastocytosis (SM) comprises a group of rare disorders resulting from tissue infiltration by pathological mast cells. In a percentage ranging from 5 to 40% in various patient series, SM appears to be associated with an accompanying hematologic neoplasm (SM-AHN). The coexistence of SM with chronic myelogenous leukemia (CML) is extremely rare with only 3 cases in the literature. The natural course of CML has changed dramatically over the past 2 decades with the use of tyrosine kinase inhibitors (TKIs). We report a case of diagnosing SM in a patient in complete molecular remission of CML after stopping TKI treatment.